Effect of Recruitment on Employee Performance - Eva Yanti; Intan Rahmayuni Syafitri; Taufik Hendra; Sufyarma Marsidin; Nellitawati Nellitawati; Prozoe Rezo (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Employees are the most important part to achieve the goals of a company or organization. So that the company runs effectively and efficiently, the company needs employees who are in accordance with the principle of